Composite microbial agent improves cotton yield and resource use efficiency under mild salt stress by optimizing plant resource allocation - Xiao Zhao; Panpan Guo; Xiong Wu; Meng Zhu; Shaozhong Kang; Taisheng Du; Jian Kang; Jinliang Chen; Ling Tong; Risheng Ding; Wanli Xu; Guangmu Tang (Agricultural Water Management)
Soil salinization and low resource utilization efficiency present significant challenges to cotton production. The application of salt-tolerant composite plant growth-promoting rhizobacteria (STC-PGPR) is considered an effective strategy to address these issues. However, its broad adaptability and regulatory mechanisms require further exploration. We hypothesize that under non-saline or moderately saline conditions, STC-PGPR directs resources to shoots, especially reproductive organs, by altering the rhizosphere bacterial community, thereby enhancing seed cotton yield (SY) and resource use efficiency. To validate our hypothesis, we conducted an experiment using two cotton varieties: Xinluzao 72 (G1) and Zhongmiansuo 49 (G2); two microbial treatments: without STC-PGPR (B1) and with STC-PGPR (B2); and three salinity levels: 0, 4, and 8 g NaCl kg−1 soil (S1, S2, S3). The results demonstrated that STC-PGPR enhanced SY and resource use efficiency under both S1 and S2 salinity levels, with significant improvements observed in G2S1 and G1S2 . Under G2S1, STC-PGPR increased nitrogen uptake efficiency, optimized shoot resource allocation to stems and squares, enhanced stem support, and improved resource storage and transport. Consequently, SY and nitrogen partial factor productivity (NPFP) increased by 9.1 % and 9.0 %, respectively. Under G1S2, STC-PGPR reduced the root-shoot ratio, directing more resources to shoots, which led to increases in SY, irrigation water productivity, and NPFP by 46.2 %, 44.8 %, and 45.9 %, respectively. These changes were primarily due to altered indigenous biomarkers after STC-PGPR application, rather than the bacteria in STC-PGPR. This study highlights the potential of STC-PGPR, emphasizing the importance of optimizing resource allocation rather than merely promoting growth. Additionally, it underscores the significant role of indigenous biomarkers in mediating these effects.